Pengembangan Modul Matematika Bernuansa Islam dan Lingkungan pada Materi Bilangan Bulat - Elsa Tia Ariski; Rizki Wahyu Yunian Putra; Arini Alhaq (Departement of Mathematics Education, 2023)
The development research was conducted as an innovation of learning modules with Islamic nuances and the environment of whole number material at the junior high school / MTs level that are feasible, interesting, and effective for use in learning. The development model used is the ADDIE model. The data analysis technique used is the analysis of validation of material, media, and religious experts, the response of the attractiveness of educators and students, and the effectiveness test. The feasibility test was conducted by three material expert validators, three media experts, and one religious expert. Attractiveness and effectiveness response tests were conducted at SMP Swadiri 1 Seputih Agung and MTs Darussalam Adijaya. The results of the feasibility test by material expert validators 3.53, media experts 3.69, and religious experts 3.77 with the criteria